Image and signal processing : 6th International Conference, ICISP 2014, Cherbourg, France, June 30 - July 2, 2014. Proceedings - Lezoray, Olivier; Nouboud, Fathallah; Mammass, Driss; Elmoataz, Abderrahim (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the 6th International Conference, ICISP 2014, held in June/July 2014 in Cherbourg, France. The 76 revised full papers were carefully reviewed and selected from 164 submissions. The contributions are organized in topical sections on multispectral colour science, color imaging and applications, digital cultural heritage, document image analysis, graph-based representations, image filtering and representation, computer vision and pattern recognition, computer graphics, biomedical, and signal processing.